'We're all poor nuts and things happen, and we just get mixed in wrong, that's all' lessons for psychotherapy from Eugene O'Neill's play, Anna Christie. Issue 2 (2nd April 2016) - Weegmann, Martin
Abstract : Anna Christie, by the Irish American playwright Eugene O'Neil, is a powerful play, depicting hurt emotions, injured selves and the hardened exteriors that people fashion to blame and afford a measure of protection. It relays the story of an abandoned daughter and her reunion with her father, their (relative) reconciliation, and meeting a new man, and the consequences of her revelation of prostitution. From textual analysis of the play, the paper explores themes of shame, repudiation and self-protection, including the formidable, or ultimate defence of 'unassailability'. It is argued that the psychotherapist has something valuable to learn from this harrowing and evocative work of literature.